Sustainability in the lower Jaguaribe Region: typological characterization of mineral grade two - Oliveira, Petronio Silva de; Oliveira, Ulisses Costa; Sousa, Adriano C. de; Martins, Renata Nascimento (Revista Hipótese, 2017)
The research was conducted in an area of 48.76 hectares, located in the Lower Jaguaribe region east of Ceara. The work consisted of the technological characterization of clays to determine parameters of the industrial volume and quality.
Keywords: Diffraction; Sustainability; Clay